KRIMINALISASI KEBIJAKAN (BELEID) TERHADAP PEJABAT PEMERINTAH DALAM TINDAK PIDANA ADMINISTRATIVE CORRUPTION: (Kajian Terhadap Putusan No. 20/Pid.Sus-TPK/2019/PN.Mtr) - Basri Mulyani (Fakultas Hukum Universitas Gunung Rinjani, 2019)
This article aims to examine the case of the distribution of clothing and food packages phase II in East Lombok Regency, or better known as Eid packages in terms of the legal considerations of the judge's decision. The point of policy confusion in state administrative law with criminal law or better known as administrative corruption. Government officials who must implement the policy, when the program is running, must deal with the criminalization of the policies that it implements. Based on these issues it is interesting to discuss related to the legal considerations of the judge's decision to release the accused and whether all government officials have the right to discretion in carrying out their positions. The research method used is a descriptive normative method, with a statutory approach, a conceptual approach and a case approach. The results of the discussion revealed that criminal law is used carefully and operationalized truly as the last drug (ultimum remedium) and not necessarily used as the main drug (primum remedium) so that government officials are no longer afraid to carry out work in the public interest and community welfare.